EMOTIONAL MODUS OF POLITICAL COMMUNICATION - N. V. Kazarinova; A. M. Ogorodnova (Дискурс, 2016)
The article is devoted to the analytical potential of the "negative communication" concept in sociological and political studies. The basic idea is that the emotional component of social action reveals structural and dynamic problems of any communicative interaction. The possibilities of the "negative communication" concept in the framework of pragmatically-oriented approach are shown by the example of some media publications devoted to interaction of politicians and ordinary citizens.